Baselining pollution: producing 'natural soil' for an environmental risk assessment exercise in Chile. Issue 3 (4th May 2018) - Ureta, Sebastián
ABSTRACT: Baselines are used extensively in environmental regulation and usually serve as a proxy of a certain 'natural' environment upon which the potential toxicity of a certain substance is assessed. However, there is nothing natural or automatic about the process via which baselines are created. Most of the time they are produced through a series of baselining practices in which heterogeneous entities are assembled in highly idiosyncratic ways, a process always crisscrossed by technical, political and ethical issues. This particular paper, based on material collected while observing an environmental risk assessment exercise carried out in an abandoned mining waste dump in northern Chile, looks at two kinds of practices that are especially salient. On the one hand, there is the recognition of a certain 'naturalness' of a particular piece of soil, a process in which visual valuation processes play a central role. On the other hand, there is the creation of 'traceability, ' through which the particular extracted sample is linked to a series of entities, gaining in the process validity as representative of the 'natural soil' existing in this particular patch. In the conclusion, both operations will be connected with different difficulties that current environmental regulation faces in dealing with polluted sites such as the one under study.